Perception of education quality in private universities of Bangladesh: A study from students' perspective - Akareem, Husain Salilul; Hossain, Syed Shahadat (2016)
This article was published in the Journal of Marketing for Higher Education [© 2012 Copyright Taylor and Francis Group, LLC.] and the definite version is available at : http://dx.doi.org/10.1080/08841241.2012.705792 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1080/08841241.2012.705792?journalCode=wmhe20